Pain Management in Patients With Lumbar Pain Syndrome Through Combined Physical and Kinetic Therapies - S. Toma; G. Toma; C.I. Neagoe; R. Rabolu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The aim of this study is to highlight the importance of associating various means of electrotherapy and kinesiotherapy in patients with low back pain. The study included 30 patients, diagnosed with low back pain syndrome, who underwent a complex treatment of physical therapy and kinesiotherapy associated with drug treatment. A questionnaire based on a series of standard questions, marked with 0-5 points, ranging from no pain and reduced functionality to intense pain and functional impairment, was used to quantify the intensity of pain and limitation of functionality due to pain. Data centralization, analysis, and comparison allowed us to identify the dynamic evolution of the monitored parameters so that after the application of associated therapies we found that if at the beginning of the treatment the majority of patients 70% (21 cases) were in severity class I established on the basis of the scores obtained by the patients in the questionnaire applied, at the end of the treatment only 13.3% (4 cases) remained in severity class I. In conclusion, the use of electrotherapy ensures the rapid achievement of optimal local conditions in the affected structures, removing the algesic component and thus preparing them for the kinetic program, thus creating a perfect symbiosis between the two methods of recovery of patients with low back pain syndrome.